Employee engagement factor for organizational excellence - Tzvetana Stoyanova; Ivaylo Iliev (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The objective of this publication is to identify ways to increase employee engagement in Bulgarian business organizations and identify how such employee engagement affects employee and company performance. Design/methodology/approach: Our research is based on the evaluation of employee engagement methodologies used by well-known companies such as Gallup HCM Advisory Group, Deloitte and Aon Hewitt. Based on these, we derive the factors influencing employee engagement in Bulgarian companies. Findings: This work focuses on management, in recent years, aimed at retaining and developing the best employees, and their evolution into reliable potential leaders of the organization. This is undertaken to maintain and increase the number of those engaged in the business of company employees as well. The management of a successful leader is considered key to increasing employee engagement. Employee commitment implies something special, additional or atypical in the performance of tasks and job role. This is a behaviour that involves innovation, demonstrating initiative via proactive seeking of opportunities that contribute to the company and exceeding the expected standard of employee performance. The findings can strengthen the already-significant role of management. There is no universal way to increase employee engagement and motivation towards increased productivity, activity, and creativity. Research limitations/implications: The study has been undertaken for employees in Bulgaria.
Keywords: M1; 330; Employee engagement; Human resources; Leadership